Lithium-rich manganese-based lithium ion secondary battery positive plate, battery and manufacturing system

A 7-layer lithium-rich manganese-based lithium-ion secondary battery electrode sheet addresses structural and high voltage issues by using aramid and vitamin coatings to prevent diaphragm aging and electrolyte reactions, enhancing cycle life and performance.

CN119181768APending Publication Date: 2024-12-24DALIAN CBAK POWER BATTERY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411305273.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Layered lithium-rich manganese-based cathode materials suffer from structural transformation and high voltage issues, leading to rapid decay in battery performance due to direct contact with the diaphragm and reaction with electrolyte, which limits their commercialization.

Method used

A 7-layer lithium-rich manganese-based lithium-ion secondary battery positive electrode sheet is constructed with aluminum foil sandwiched between multiple layers of positive electrode slurry coatings, aramid coatings, and vitamin coatings, which act as oxygen scavengers and electrolyte stabilizers to prevent direct contact and reactions.

Benefits of technology

The layered structure enhances the cycle life of the battery by preventing diaphragm aging and reducing oxygen atom reactions with the electrolyte, thereby improving overall performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181768A_ABST
    Figure CN119181768A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of battery production, and discloses a lithium-rich manganese-based lithium ion secondary battery positive plate, a battery and a manufacturing system.The lithium-rich manganese-based lithium ion secondary battery positive plate comprises an aluminum foil, a first positive slurry coating layer is arranged on the upper surface of the aluminum foil, and a second positive slurry coating layer is arranged on the lower surface of the aluminum foil; a first aramid fiber coating layer is arranged on the upper surface of the first positive electrode slurry coating layer, and a second aramid fiber coating layer is arranged on the lower surface of the second positive electrode slurry coating layer. According to the lithium ion battery, the aramid fiber functional layer is used for blocking direct contact between the positive electrode material and the diaphragm and preventing aging of the diaphragm, vitamins in the vitamin functional layer are used for active oxygen atom capturing agents and inhibiting or reducing reaction between oxygen atoms and electrolyte, and nano aluminum oxide in the vitamin functional layer is used for effectively storing the electrolyte and facilitating lithium ion conduction. The combination of the two prolongs the cycle life of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery production, and in particular to a lithium-rich manganese-based lithium-ion secondary battery positive electrode sheet, a battery and a manufacturing system. Background Art

[0002] At present, the main cathode materials for commercial lithium-ion batteries are lithium manganese oxide (LiMn2O4), lithium iron phosphate (LiFePO4), lithium cobalt oxide (LiCoO2), nickel cobalt manganese oxide (NCM) and nickel cobalt aluminum oxide (NCA), with actual specific capacities ranging from 110 to 200 mA·h / g; however, the specific capacity of commercialized anode materials is very high, ranging from 3 to 20 times that of cathode materials, which makes cathode materials become the bottleneck for further improving the performance of lithium-ion batteries;

[0003] However, the existing processing equipment has the following shortcomings:

[0004] Layered lithium-rich manganese-based materials (LMR) are expected to become the cathode materials of the new generation of lithium-ion batteries due to their high specific capacity (>250mAh / g) and low cost. However, since their discovery nearly 30 years ago, they have never been truly commercialized. The main reasons are: 1. During the cycle, Mn 3+ It will migrate to the lithium vacancies, causing the layered structure to transform into a spinel structure, resulting in a continuous decrease in the average discharge voltage, causing serious energy loss, and also bringing huge challenges to battery management; 2. LMR materials can only exert their high capacity under high voltage (>4.55V). Under high voltage, the LMR material is in direct contact with the diaphragm, which will cause aging of the diaphragm and closed pores, and the battery's rate charge and discharge performance will decrease, and the cycle life will decay rapidly; at the same time, the positive electrode material will release active oxygen atoms at high voltage, and the active oxygen atoms will react with the electrolyte, and the cycle life will also decay rapidly.

[0005] In order to overcome the above-mentioned defects, the present application invents a lithium-rich manganese-based secondary battery positive electrode plate, a battery and a system thereof, which effectively inhibits the aging of the lithium-rich manganese-based positive electrode material on the diaphragm and the reaction with the electrolyte, and effectively improves the cycle life of the lithium-rich manganese-based lithium ion secondary battery. Summary of the invention

[0006] The object of the present invention is to provide a lithium-rich manganese-based lithium-ion secondary battery positive electrode sheet, a battery and a manufacturing system to solve the problems raised by the above background technology.

[0007] To solve the technical problem, the present invention is achieved through the following technical scheme: a lithium-manganese-rich lithium-ion secondary battery positive electrode sheet and a battery, comprising an aluminum foil, wherein a first positive electrode slurry coating layer is provided on the upper surface of the aluminum foil, and a second positive electrode slurry coating layer is provided on the lower surface of the aluminum foil, a first aramid coating layer is provided on the upper surface of the first positive electrode slurry coating layer, and a second aramid coating layer is provided on the lower surface of the second positive electrode slurry coating layer, a first vitamin coating layer is provided on the upper surface of the first aramid coating layer, and a second vitamin coating layer is provided on the lower surface of the second aramid coating layer.

[0008] Furthermore, it includes an unwinding shaft and a transfer shaft, the number of the transfer shafts is two, the two transfer shafts are arranged on the right side of the unwinding shaft, a slurry coating area is arranged on the right side of the two transfer shafts, a second slurry coating device is arranged inside the slurry coating area, a first slurry coating device is arranged inside the slurry coating area, a first drying device is arranged on the right side of the slurry coating area, an aramid coating area is arranged on the right side of the first drying device, a first micro-gravure coating device is arranged inside the aramid coating area, and a second micro-gravure coating device is arranged inside the aramid coating area.

[0009] Furthermore, a second drying device and a coating device are arranged on the right side of the aramid coating area, and a vitamin coating area is arranged on the right side of the second drying device and a coating device.

[0010] Furthermore, a third micro-gravure coating device is disposed inside the vitamin coating area, and a fourth micro-gravure coating device is disposed inside the vitamin coating area.

[0011] Furthermore, a third drying device is arranged on the right side of the vitamin coating area, and a winding shaft is arranged on the right side of the third drying device.

[0012] Furthermore, a rolled-up aluminum foil is arranged inside the unwinding shaft, and the aluminum foil is displaced and moved through the surfaces of two transfer shafts.

[0013] Furthermore, the aluminum foil enters a slurry coating area, and a positive electrode slurry coating layer is coated on the surface of the aluminum foil through a first slurry coating device and a second slurry coating device inside the slurry coating area.

[0014] Further, the coated aluminum foil is dried by a first drying device for three minutes at a drying temperature of one hundred and fifteen degrees Celsius, and the aluminum foil passes through an aramid coating area.

[0015] Furthermore, the aramid coating area is subjected to secondary coating of the coated aluminum foil by the first micro-gravure coating device and the second micro-gravure coating device, and the aluminum foil is subjected to secondary drying by the second drying device coating device.

[0016] Furthermore, the aluminum foil enters the vitamin coating area and is coated by the third micro-gravure coating device and the fourth micro-gravure coating device. The aluminum foil is dried by the third drying device and is rolled up by the winding shaft.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The positive electrode plate provided by the present invention is composed of a 7-layer structure; the middle layer is aluminum foil, the positive electrode slurry coating layer (the second layer and the third layer) is closely attached to the upper and lower surfaces of the aluminum foil, the aramid functional layer (the fourth layer and the fifth layer) is closely attached to the positive electrode slurry coating layer, and the vitamin functional layer (the sixth layer and the seventh layer) is closely attached to the aramid functional layer.

[0019] The function of the aramid functional layer is to prevent the direct contact between the positive electrode material and the diaphragm to prevent aging of the diaphragm. The vitamin in the vitamin functional layer acts as an active oxygen atom scavenger to inhibit or reduce the reaction between oxygen atoms and the electrolyte. The function of the nano-alumina in the vitamin functional layer is to effectively preserve the electrolyte and facilitate lithium ion conduction. The combination of the two improves the cycle life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a structural schematic diagram of a sodium ion positive electrode sheet preparation system of a lithium-rich manganese-based lithium ion secondary battery positive electrode sheet, a battery and a manufacturing system of the present invention;

[0021] Figure 2 This is a structural diagram of a sodium ion positive electrode sheet of a lithium-rich manganese-based lithium ion secondary battery positive electrode sheet, a battery and a manufacturing system of the present invention;

[0022] Figure 3 The present invention is a schematic diagram of an experimental comparison of a lithium-rich manganese-based lithium-ion secondary battery positive electrode sheet, a battery and a manufacturing system.

[0023] In the figure: 1. unwinding shaft; 2. transfer shaft; 3. slurry coating area; 4. first slurry coating equipment; 5. second slurry coating equipment; 6. first drying equipment; 7. aramid coating area; 8. first micro-gravure coating equipment; 9. second micro-gravure coating equipment; 10. second drying equipment; 11. vitamin coating area; 12. third micro-gravure coating equipment; 13. fourth micro-gravure coating equipment; 14. third drying equipment; 15. winding shaft; 16. first vitamin coating layer; 17. first aramid coating layer; 18. first positive electrode slurry coating layer; 19. aluminum foil; 20. second positive electrode slurry coating layer; 21. second aramid coating layer; 22. second vitamin coating layer. DETAILED DESCRIPTION

[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the implementation regulations described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] See also Figure 1-Figure 2 As shown, the present invention provides a technical solution: comprising an aluminum foil 19, wherein a first positive electrode slurry coating layer 18 is provided on the upper surface of the aluminum foil 19, a second positive electrode slurry coating layer 20 is provided on the lower surface of the aluminum foil 19, a first aramid coating layer 17 is provided on the upper surface of the first positive electrode slurry coating layer 18, a second aramid coating layer 21 is provided on the lower surface of the second positive electrode slurry coating layer 20, a first vitamin coating layer 16 is provided on the upper surface of the first aramid coating layer 17, and a second vitamin coating layer 22 is provided on the lower surface of the second aramid coating layer 21.

[0026] Specifically, it includes an unwinding shaft 1 and a transfer shaft 2, there are two transfer shafts 2, the two transfer shafts 2 are located on the right side of the unwinding shaft 1, a slurry coating area 3 is arranged on the right side of the two transfer shafts 2, a second slurry coating device 5 is arranged inside the slurry coating area 3, a first slurry coating device 4 is arranged inside the slurry coating area 3, a first drying device 6 is arranged on the right side of the slurry coating area 3, an aramid coating area 7 is arranged on the right side of the first drying device 6, a first micro-gravure coating device 8 is arranged inside the aramid coating area 7, and a second micro-gravure coating device 9 is arranged inside the aramid coating area 7.

[0027] Specifically, a second drying device coating device 10 is disposed on the right side of the aramid coating area 7 , and a vitamin coating area 11 is disposed on the right side of the second drying device coating device 10 .

[0028] Specifically, a third micro-gravure coating device 12 is disposed inside the vitamin coating area 11 , and a fourth micro-gravure coating device 13 is disposed inside the vitamin coating area 11 .

[0029] Specifically, a third drying device 14 is disposed on the right side of the vitamin coating area 11 , and a winding shaft 15 is disposed on the right side of the third drying device 14 .

[0030] Specifically, a rolled-up aluminum foil 19 is disposed inside the unwinding shaft 1 , and the aluminum foil 19 is displaced and moved through the surfaces of the two transfer shafts 2 .

[0031] Specifically, the aluminum foil 19 enters the slurry coating area 3 , and the positive electrode slurry coating layer is coated on the surface of the aluminum foil 19 through the first slurry coating device 4 and the second slurry coating device 5 inside the slurry coating area 3 .

[0032] Specifically, the coated aluminum foil 19 passes through the first drying device 6 for a drying time of three minutes and a drying temperature of one hundred and fifteen degrees Celsius, and the aluminum foil 19 passes through the aramid coating area 7.

[0033] Specifically, the aramid coating area 7 performs secondary coating on the coated aluminum foil 19 through the first micro-gravure coating device 8 and the second micro-gravure coating device 9, and the aluminum foil 19 is secondary dried through the second drying device coating device 10.

[0034] Specifically, the aluminum foil 19 enters the vitamin coating area 11 and is coated by the third micro-gravure coating device 12 and the fourth micro-gravure coating device 13. The aluminum foil 19 is dried by the third drying device 14, and the aluminum foil 19 is reeled up by the reeling shaft 15.

[0035] A positive electrode slurry coating layer

[0036] 1) Coat the positive electrode slurry on the aluminum foil at a coating speed of 10-30m / min, a drying temperature of 80-130℃, and a drying time of 3-5min. The positive electrode slurry consists of four parts: positive electrode active material, conductive agent, binder, and NMP. The positive electrode active material can be one of sodium vanadium phosphate, sodium nickel cobalt manganese oxide, and Prussian blue compounds; the conductive agent can be one or more of acetylene black, carbon black, carbon nanotubes, and graphene; the binder can be one of polyvinylidene fluoride and polyacrylic acid; the solid content of the slurry is controlled between 45-65%;

[0037] 2) The dried coated sheet in step 1 is rolled and cut to obtain a positive electrode slurry coating layer.

[0038] Preparation of diaramid functional layer slurry

[0039] 1) Place the aramid raw material in a 500L tank, and add the organic solvent evenly in three times. After each solvent addition, the stirring paddle speed is 10-40r / min, the dispersion disk linear speed is 15-50m / s, and the running time is 30-60min;

[0040] 2) After step 2, an aramid solution with a solid content of 6-20% is obtained;

[0041] The aramid raw material is one or both of poly(m-phenylene isophthalamide) fiber (referred to as meta-aramid) or poly(p-phenylene terephthalamide) fiber (referred to as para-aramid); the organic solvent is one or more of N-methylpyrrolidone (NMP), N,N-dimethylacetamide (DMAC), and N,N-dimethylformamide (DMF).

[0042] Preparation of Tri-vitamin Functional Layer Slurry

[0043] 1) Dry mix the vitamins, alumina, binder and dispersant in a 200L V-type mixer for 30-60 minutes;

[0044] 2) The mixture in 1) was transferred to a 600L slurry mixing tank, and NMP was added evenly in three times. After each addition of NMP, the stirring paddle speed was 10-40r / min, the dispersion disk linear speed was 15-50m / s, and the running time was 30-60min;

[0045] 3) After step 2, a functional slurry with a solid content of 6-20% is obtained;

[0046] 1) The vitamin is vitamin C or vitamin E; the binder can be one or both of polyvinylidene fluoride and polyacrylate; the dispersant can be one or both of polyvinyl pyrrolidone and sodium polyacrylate.

[0047] 1) The mass proportions of vitamin, alumina, binder and dispersant are 10-90:10-90:1-5:0.1-2.

[0048] Four functional layer coating

[0049] 1) The aramid functional layer slurry is coated on the positive electrode slurry coating layer in a micro-gravure coater to obtain a composite coating 1, and the single-layer wet film thickness is controlled at 2-5 μm; the coating speed is 20-100 m / min, the drying temperature is 60-100° C., and the drying time is 0.5-2 min; after drying, the thickness of the single-layer functional layer is controlled at 1-3 μm.

[0050] 2) The vitamin functional layer slurry is coated on the composite coating 1 in a micro-gravure coater, and the single-layer wet film thickness is controlled at 2-5 μm; the coating speed is 20-100 m / min, the drying temperature is 80-130° C., and the drying time is 0.5-2 min; after drying, the thickness of the single-layer functional layer is controlled at 0.5-1.5 μm.

[0051] After the functional coating layer is completed, the final lithium-rich manganese-based lithium-ion secondary battery positive electrode sheet is obtained.

[0052] Preparation of five lithium-rich manganese-based secondary batteries

[0053] 1. The present invention provides a lithium-rich manganese-based secondary battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the positive electrode sheet is the above-mentioned positive electrode sheet;

[0054] 2. The negative electrode sheet is composed of four parts: negative electrode active material, conductive agent, binder, and current collector. The negative electrode active material is hard carbon material; the conductive agent can be one or more of acetylene black, carbon black, carbon nanotubes, and graphene; the binder is CMC and SBR; the current collector is copper foil or aluminum foil;

[0055] 3. The diaphragm can be one of polyethylene, polypropylene, polyvinylidene fluoride, and aramid;

[0056] The electrolyte is composed of an organic solvent and an electrolyte lithium salt. As an example, the organic solvent may be one or more of ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, propylene carbonate, methyl acetate, ethyl propionate, fluoroethylene carbonate, ethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, and methyl tert-butyl ether; the electrolyte sodium salt may be one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethanesulfonyl imide), lithium trifluoromethanesulfonate, lithium tetrafluoroborate, lithium difluorophosphate, and lithium perchlorate.

[0057] Example 1

[0058] A positive electrode slurry coating layer

[0059] 1) Coat the positive electrode slurry on the aluminum foil at a coating speed of 20m / min, a drying temperature of 115°C, and a drying time of 3min. The positive electrode slurry consists of four parts: positive electrode active material, conductive agent, binder, and NMP. The positive electrode active material is a lithium-rich manganese-based positive electrode material; the conductive agent is acetylene black; the binder is polyvinylidene fluoride, and the mass ratio of the three is 96:2:2; the slurry solid content is 53.2%;

[0060] 2) The dried coated sheet in step 1 is rolled and cut to obtain a positive electrode slurry coating layer.

[0061] Preparation of diaramid functional layer slurry

[0062] 1) 25 kg of meta-aramid raw material was placed in a 500 L tank, and DMAC was evenly added in three times. After each solvent addition, the stirring paddle speed was 30 r / min, the dispersion disk linear speed was 35 m / s, and the running time was 50 min;

[0063] 2) After step 2, an aramid solution with a solid content of 6.2% is obtained;

[0064] Preparation of three vitamin functional layer slurry

[0065] 1) Vitamin C, alumina, binder and dispersant were dry mixed in a 200LV mixer for 60 minutes; the weight ratio of conductive agent, polymer blocker, binder and dispersant was 20:78:1.5:0.5, and the total weight of the above substances was 70 kg. The binder was polyvinylidene fluoride and the dispersant was polyvinyl pyrrolidone.

[0066] 2) The mixture in 1) was transferred to a 600L slurry mixing tank, and NMP was added evenly in three times. After each addition of NMP, the stirring paddle speed was 30r / min, the dispersion disk linear speed was 40m / s, the operation time was 60min, and the total amount of NMP added was 386.74Kg;

[0067] After step 2, a functional layer slurry with a solid content of 18.1% is obtained;

[0068] Four functional layer coating

[0069] The aramid functional layer slurry is coated on the positive electrode slurry in a micro-gravure coater to obtain a composite coating 1, and the single-layer wet film thickness is controlled at 2.5-3.0 μm; the coating speed is 40 m / min, the drying temperature is 100° C., and the drying time is 2 min; after drying, the thickness of the single-layer functional layer is controlled at 1.2-1.5 μm.

[0070] The vitamin functional layer slurry is coated on the composite coating 1 in a micro-gravure coater, and the single-layer wet film thickness is controlled at 1.5-2.5 μm; the coating speed is 20 m / min, the drying temperature is 90° C., and the drying time is 1.5 min; after drying, the thickness of the single-layer functional layer is controlled at 0.8-1.5 μm.

[0071] After the functional coating layer is completed, the final lithium-rich manganese-based lithium-ion secondary battery positive electrode sheet is obtained.

[0072] Example 2

[0073] A positive electrode slurry coating layer

[0074] 1) Coat the positive electrode slurry on the aluminum foil at a coating speed of 20m / min, a drying temperature of 115°C, and a drying time of 3min. The positive electrode slurry consists of four parts: positive electrode active material, conductive agent, binder, and NMP. The positive electrode active material is a lithium-rich manganese-based positive electrode material; the conductive agent is acetylene black; the binder is polyvinylidene fluoride, and the mass ratio of the three is 96:2:2; the slurry solid content is 53.2%;

[0075] 2) The dried coated sheet in step 1 is rolled and cut to obtain a positive electrode slurry coating layer.

[0076] Preparation of diaramid functional layer slurry

[0077] 1) 25 kg of para-aramid raw material was placed in a 500 L tank, and DMAC was evenly added in three times. After each solvent addition, the stirring paddle speed was 30 r / min, the dispersion disk linear speed was 35 m / s, and the running time was 50 min;

[0078] 2) After step 2, an aramid solution with a solid content of 3.0% is obtained;

[0079] Preparation of three vitamin functional layer slurry

[0080] 3) Vitamin E, alumina, a binder, and a dispersant are dry mixed in a 200LV mixer for 60 minutes; the weight ratio of the conductive agent, polymer blocker, binder, and dispersant is 50:48:1.5:0.5, and the total weight of the above substances is 50 kg. The binder is polyvinylidene fluoride and the dispersant is polyvinyl pyrrolidone.

[0081] 4) The mixture in 1) was transferred to a 600L slurry mixing tank, and NMP was added evenly in three times. After each addition of NMP, the stirring paddle speed was 30r / min, the dispersion disk linear speed was 40m / s, the running time was 60min, and the total amount of NMP added was 326.79Kg;

[0082] After step 2, a functional layer slurry with a solid content of 15.3% is obtained;

[0083] Four functional layer coating

[0084] The aramid functional layer slurry is coated on the positive electrode slurry in a micro-gravure coater to obtain a composite coating 1, and the single-layer wet film thickness is controlled at 2.5-3.0 μm; the coating speed is 40 m / min, the drying temperature is 100° C., and the drying time is 2 min; after drying, the thickness of the single-layer functional layer is controlled at 1.2-1.5 μm.

[0085] The vitamin functional layer slurry is coated on the composite coating 1 in a micro-gravure coater, and the single-layer wet film thickness is controlled at 1.5-2.5 μm; the coating speed is 20 m / min, the drying temperature is 90° C., and the drying time is 1.5 min; after drying, the thickness of the single-layer functional layer is controlled at 0.8-1.5 μm.

[0086] After the functional coating layer is completed, the final lithium-rich manganese-based lithium-ion secondary battery positive electrode sheet is obtained.

[0087] Example 3

[0088] A positive electrode slurry coating layer

[0089] 1) Coat the positive electrode slurry on the aluminum foil at a coating speed of 20m / min, a drying temperature of 115°C, and a drying time of 3min. The positive electrode slurry consists of four parts: positive electrode active material, conductive agent, binder, and NMP. The positive electrode active material is a lithium-rich manganese-based positive electrode material; the conductive agent is acetylene black; the binder is polyvinylidene fluoride, and the mass ratio of the three is 96:2:2; the slurry solid content is 53.2%;

[0090] 2) The dried coated sheet in step 1 is rolled and cut to obtain a positive electrode slurry coating layer.

[0091] Preparation of diaramid functional layer slurry

[0092] 1) 25 kg of para-aramid raw material was placed in a 500 L tank, and DMAC was evenly added in three times. After each solvent addition, the stirring paddle speed was 30 r / min, the dispersion disk linear speed was 35 m / s, and the running time was 50 min;

[0093] 2) After step 2, an aramid solution with a solid content of 3.0% is obtained;

[0094] Preparation of three vitamin functional layer slurry

[0095] 5) Vitamin C, alumina, binder and dispersant were dry mixed in a 200LV mixer for 60 minutes; the weight ratio of conductive agent, polymer blocker, binder and dispersant was 72:26:1.5:0.5, and the total weight of the above substances was 50 kg. The binder was polyvinylidene fluoride and the dispersant was polyvinyl pyrrolidone.

[0096] 6) The mixture in 1) was transferred to a 600L slurry mixing tank, and NMP was added evenly in three times. After each addition of NMP, the stirring paddle speed was 30r / min, the dispersion disk linear speed was 40m / s, the running time was 60min, and the total amount of NMP added was 362.32Kg;

[0097] After step 2, a functional layer slurry with a solid content of 13.8% is obtained;

[0098] Four functional layer coating

[0099] The aramid functional layer slurry is coated on the positive electrode slurry in a micro-gravure coater to obtain a composite coating 1, and the single-layer wet film thickness is controlled at 2.5-3.0 μm; the coating speed is 40 m / min, the drying temperature is 100° C., and the drying time is 2 min; after drying, the thickness of the single-layer functional layer is controlled at 1.2-1.5 μm.

[0100] The vitamin functional layer slurry is coated on the composite coating 1 in a micro-gravure coater, and the single-layer wet film thickness is controlled at 1.5-2.5 μm; the coating speed is 20 m / min, the drying temperature is 90° C., and the drying time is 1.5 min; after drying, the thickness of the single-layer functional layer is controlled at 0.8-1.5 μm.

[0101] After the functional coating layer is completed, the final lithium-rich manganese-based lithium-ion secondary battery positive electrode sheet is obtained.

[0102] Comparative Examples 1-3

[0103] In Example 1-3, the positive electrode current collector is replaced with aluminum foil, and the rest is the same.

[0104] Comparative Example 4

[0105] A positive electrode slurry coating layer

[0106] 1) Coat the positive electrode slurry on the aluminum foil at a coating speed of 20m / min, a drying temperature of 115°C, and a drying time of 3min. The positive electrode slurry consists of four parts: positive electrode active material, conductive agent, binder, and NMP. The positive electrode active material is a lithium-rich manganese-based positive electrode material; the conductive agent is acetylene black; the binder is polyvinylidene fluoride, and the mass ratio of the three is 96:2:2; the slurry solid content is 53.2%;

[0107] 2) The dried coated sheet in step 1 is rolled and cut to obtain a positive electrode slurry coating layer.

[0108] Preparation of diaramid functional layer slurry

[0109] 1) 25 kg of meta-aramid raw material was placed in a 500 L tank, and DMAC was evenly added in three times. After each solvent addition, the stirring paddle speed was 30 r / min, the dispersion disk linear speed was 35 m / s, and the running time was 50 min;

[0110] 2) After step 2, an aramid solution with a solid content of 6.2% is obtained;

[0111] Four functional layer coating

[0112] The aramid functional layer slurry is coated on the positive electrode slurry in a micro-gravure coater to obtain a composite coating 1, and the single-layer wet film thickness is controlled at 2.5-3.0 μm; the coating speed is 40 m / min, the drying temperature is 100° C., and the drying time is 2 min; after drying, the thickness of the single-layer functional layer is controlled at 1.2-1.5 μm.

[0113] After the functional coating layer is completed, the final lithium-rich manganese-based lithium-ion secondary battery positive electrode sheet is obtained.

[0114] Comparative Example 5

[0115] A positive electrode slurry coating layer

[0116] 1) Coat the positive electrode slurry on the aluminum foil at a coating speed of 20m / min, a drying temperature of 115°C, and a drying time of 3min. The positive electrode slurry consists of four parts: positive electrode active material, conductive agent, binder, and NMP. The positive electrode active material is a lithium-rich manganese-based positive electrode material; the conductive agent is acetylene black; the binder is polyvinylidene fluoride, and the mass ratio of the three is 96:2:2; the slurry solid content is 53.2%;

[0117] 2) The dried coated sheet in step 1 is rolled and cut to obtain a positive electrode slurry coating layer.

[0118] Preparation of Vitamin Functional Layer Slurry

[0119] 1) Vitamin C, alumina, binder and dispersant were dry mixed in a 200LV mixer for 60 minutes; the weight ratio of conductive agent, polymer blocker, binder and dispersant was 20:78:1.5:0.5, and the total weight of the above substances was 70 kg. The binder was polyvinylidene fluoride and the dispersant was polyvinyl pyrrolidone.

[0120] 2) The mixture in 1) was transferred to a 600L slurry mixing tank, and NMP was added evenly in three times. After each addition of NMP, the stirring paddle speed was 30r / min, the dispersion disk linear speed was 40m / s, the operation time was 60min, and the total amount of NMP added was 386.74Kg;

[0121] After step 2, a functional layer slurry with a solid content of 18.1% is obtained;

[0122] Three functional layer coating

[0123] The vitamin functional layer slurry is coated on the composite coating 1 in a micro-gravure coater, and the single-layer wet film thickness is controlled at 1.5-2.5 μm; the coating speed is 20 m / min, the drying temperature is 90° C., and the drying time is 1.5 min; after drying, the thickness of the single-layer functional layer is controlled at 0.8-1.5 μm.

[0124] After the functional coating layer is completed, the final lithium-rich manganese-based lithium-ion secondary battery positive electrode sheet is obtained.

[0125] The 32140 cylindrical lithium ion secondary batteries of Examples 1-3 and Comparative Examples 1-5 were prepared according to the following method.

[0126] 1. Preparation of positive electrode

[0127] Positive electrode sheets of Examples 1-3 and positive electrode sheets of Comparative Examples 1-5;

[0128] 2. Preparation of negative electrode sheet

[0129] 95.5wt% graphite, 1% acetylene black, 1.5% CMC, and 2% SBR are added to pure water and dispersed evenly to prepare negative electrode slurry. The negative electrode slurry is evenly coated on the surface of the copper foil, and after drying, it is rolled and cut to obtain the negative electrode;

[0130] 3. Diaphragm

[0131] The diaphragm is made of polyethylene (PE) porous polymer film.

[0132] 4. Preparation of Electrolyte

[0133] 16g of lithium hexafluorophosphate, 25g of ethylene carbonate, 52g of dimethyl carbonate, 6g of diethylene glycol dimethyl ether, and 1g of methyl methyl thiosulfonate are mixed evenly to prepare an electrolyte.

[0134] The positive electrode sheet, separator and negative electrode sheet are wound into an electrode group, and then assembled into a 32140 battery after groove rolling, liquid injection and sealing.

[0135] Cycle life test method: At 25°C, the battery prepared in the embodiment and the comparative example is charged to 4.6V at a rate of 0.5C, and discharged to 3V at a rate of 0.5C, and a full charge and discharge cycle test is performed until the capacity of the battery is less than 80% of the initial capacity, and the number of cycles is recorded. The specific data is shown in the table below. It can be seen that in Examples 1-3 and Comparative Examples 1-5, the lithium-rich manganese-based lithium-ion battery prepared by the present invention has a good cycle life; in Example 1 and Comparative Examples 4-5, the cycle life of the lithium-ion battery corresponding to the aramid coating combined with the vitamin coating is better than that of the lithium-ion battery using the aramid coating alone or the lithium-ion battery using the vitamin coating alone.

[0136] The effect achieved by the entire structure is as follows: the positive electrode plate provided by the present invention is composed of a 7-layer structure; the middle layer is aluminum foil, the positive electrode slurry coating layer (the second layer and the third layer) is closely attached to the upper and lower surfaces of the aluminum foil, the aramid functional layer (the fourth layer and the fifth layer) is closely attached to the positive electrode slurry coating layer, and the vitamin functional layer (the sixth layer and the seventh layer) is closely attached to the aramid functional layer.

[0137] The function of the aramid functional layer is to prevent the direct contact between the positive electrode material and the diaphragm to prevent aging of the diaphragm. The vitamin in the vitamin functional layer acts as an active oxygen atom scavenger to inhibit or reduce the reaction between oxygen atoms and the electrolyte. The function of the nano-alumina in the vitamin functional layer is to effectively preserve the electrolyte and facilitate lithium ion conduction. The combination of the two improves the cycle life of the battery.

[0138] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A lithium-rich manganese-based lithium-ion secondary battery positive electrode sheet and battery, characterized in that: The invention comprises an aluminum foil (19), wherein a first positive electrode slurry coating layer (18) is arranged on the upper surface of the aluminum foil (19), and a second positive electrode slurry coating layer (20) is arranged on the lower surface of the aluminum foil (19); a first aramid coating layer (17) is arranged on the upper surface of the first positive electrode slurry coating layer (18), and a second aramid coating layer (21) is arranged on the lower surface of the second positive electrode slurry coating layer (20); a first vitamin coating layer (16) is arranged on the upper surface of the first aramid coating layer (17), and a second vitamin coating layer (22) is arranged on the lower surface of the second aramid coating layer (21).

2. A manufacturing system for a lithium-rich manganese-based lithium-ion secondary battery positive electrode sheet and a battery according to claim 1, comprising an unwinding shaft (1) and a transfer shaft (2), characterized in that: There are two transfer shafts (2), the two transfer shafts (2) are arranged on the right side of the unwinding shaft (1), a slurry coating area (3) is arranged on the right side of the two transfer shafts (2), a second slurry coating device (5) is arranged inside the slurry coating area (3), a first slurry coating device (4) is arranged inside the slurry coating area (3), a first drying device (6) is arranged on the right side of the slurry coating area (3), an aramid coating area (7) is arranged on the right side of the first drying device (6), a first micro-gravure coating device (8) is arranged inside the aramid coating area (7), and a second micro-gravure coating device (9) is arranged inside the aramid coating area (7).

3. The manufacturing system of a lithium-rich manganese-based lithium-ion secondary battery positive electrode sheet and battery according to claim 2, characterized in that: A second drying device and coating device (10) is arranged on the right side of the aramid coating area (7), and a vitamin coating area (11) is arranged on the right side of the second drying device and coating device (10).

4. The manufacturing system of a lithium-rich manganese-based lithium-ion secondary battery positive electrode sheet and battery according to claim 3, characterized in that: A third micro-gravure coating device (12) is disposed inside the vitamin coating area (11), and a fourth micro-gravure coating device (13) is disposed inside the vitamin coating area (11).

5. The manufacturing system of a lithium-rich manganese-based lithium-ion secondary battery positive electrode sheet and battery according to claim 4, characterized in that: A third drying device (14) is arranged on the right side of the vitamin coating area (11), and a winding shaft (15) is arranged on the right side of the third drying device (14).

6. The manufacturing system of a lithium-rich manganese-based lithium-ion secondary battery positive electrode sheet and battery according to claim 2, characterized in that: A rolled-up aluminum foil (19) is arranged inside the unwinding shaft (1), and the aluminum foil (19) is displaced and moved through the surfaces of two transfer shafts (2).

7. A manufacturing system for a lithium-rich manganese-based lithium-ion secondary battery positive electrode sheet and a battery according to claim 6, characterized in that: The aluminum foil (19) enters the slurry coating area (3), and a positive electrode slurry coating layer is coated on the surface of the aluminum foil (19) through a first slurry coating device (4) and a second slurry coating device (5) inside the slurry coating area (3).

8. The manufacturing system of a lithium-rich manganese-based lithium-ion secondary battery positive electrode sheet and battery according to claim 7, characterized in that: The coated aluminum foil (19) is dried by a first drying device (6) for three minutes at a drying temperature of one hundred and fifteen degrees Celsius, and the aluminum foil (19) passes through an aramid coating area (7).

9. A manufacturing system for a lithium-rich manganese-based lithium-ion secondary battery positive electrode sheet and a battery according to claim 8, characterized in that: The aramid coating area (7) performs secondary coating on the coated aluminum foil (19) through a first micro-gravure coating device (8) and a second micro-gravure coating device (9), and the aluminum foil (19) is secondary dried through a second drying device coating device (10).

10. A manufacturing system for a lithium-rich manganese-based lithium-ion secondary battery positive electrode sheet and a battery according to claim 9, characterized in that: The aluminum foil (19) enters the vitamin coating area (11) and is coated by the third micro-gravure coating device (12) and the fourth micro-gravure coating device (13). The aluminum foil (19) is dried by the third drying device (14), and the aluminum foil (19) is rolled up by the winding shaft (15).

Citation Information

Cited By

  • Positive electrode structure, preparation method thereof and lithium battery

    CN121416419A